Peranan Sains Dalam Membangun Masyarakat - Putri, Cindy Asa; Firdianti, Sasa Bela; Irianty, Amanda Dwi Febri; Mahardika, I Ketut; Ernasari, Ernasari; Handono, Sri (Jurnal Ilmiah Wahana Pendidikan, 2024)
At every change in time that occurs, there are lots of things that change at any time. This is because it is influenced by a person's curiosity about something new and wanting to do it with the knowledge they have obtained. So this creates a change in the world because it is based on curiosity towards science. In making a change that is based on this knowledge, there must be an attitude of appreciation and selectivity regarding the knowledge obtained from the surrounding environment in order to avoid confusion in science. Based on this, the researcher conducted a study of several reference sources related to science related to the role of science in developing society. Because human science and science have a relationship in life, which is found in a curiosity about science. Based on this discussion, the researchers linked it to several related matters, including; the relationship between humans and science, examples of science in society, the benefits of studying science and the goals of science in society.